Safety and efficacy of an essential oil of Origanum vulgare ssp. hirtum (Link) leetsw. for all poultry species. (3rd April 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of an essential oil of Origanum vulgare ssp. hirtum (Link) leetsw. for all poultry species. The essential oil under assessment obtained ■■■■■ is specified to contain carvacrol ■■■■■ and thymol (7%). The remaining 30% of the composition remains uncharacterised. In the absence of these data, the FEEDAP Panel was unable to make a risk assessment of the additive for the target species, the consumer and the user. Use in animal production of the essential oil extracted from O. vulgare ssp. hirtum (Link) leetsw. is not expected to pose a risk for the environment. Since oregano and its extracts are universally recognised to flavour food and their function in feed would be essentially the same as that in food, no further demonstration of efficacy is considered necessary.